Christianity and human rights reconsidered - Shortall, Sarah 1985- HerausgeberIn; Steinmetz-Jenkins, Daniel 1979- HerausgeberIn (Human rights in history, 2020)
"This is the first global examination of the historical relationship between Christianity and human rights in the twentieth century. Leading historians, anthropologists, political theorists, legal scholars, and scholars of religion develop fresh approaches to issues such as human dignity, personalism, religious freedom, the role of ecumenical and transatlantic networks, and the relationship between Christian and liberal rights theories. In doing so they move well beyond the temporal and geographical limits of the existing scholarship, exploring the connection between Christianity and human rights, not only in Europe and the United States, but also in Africa, Latin America, and China. They offer alternative chronologies and bring to light overlooked aspects of this history, including the role of race, gender, decolonization, and interreligious dialogue. Above all, these essays foreground the complicated relationship between global rights discourses - whether Christian, liberal, or otherwise - and the local contexts in which they are developed and implemented"--